Aesthetic Values of Traditional Najdi Architectural Symbols in the Design of National Day (89) Advertisement Logos in Al-Diriyah (Al-Academy, 2025)
National Day is a joyful occasion for the nation, and advertisements serve as a medium to highlight aesthetic values, as seen in Saudi National Day campaigns. This research, using a descriptive-analytical approach, explores the aesthetic values of heritage symbols inspired by Najdi architecture in Diriyah and their role in designing the 89th National Day advertisement logo.A sample of National Day advertisement posters was analyzed to identify aesthetic values and their connection to heritage elements. A classification table was employed to examine the heritage symbols, focusing on the Najdi architectural features of Diriyah and their contribution to the design’s visual identity.The findings reveal that heritage symbols derived from Diriyah’s architecture carry significant aesthetic and functional roles, enhancing the overall design. Organizing relationships between design elements strengthens the aesthetic appeal of these symbols, reflecting the richness of Diriyah’s heritage and emphasizing its role in celebrating national identity.